Internal vs. external habit formation in a growing economy with overlapping generations - Masako Ikefuji; Kazuo Mino (Osaka University, Institute of Social and Economic Research (ISER), 2009)
This paper explores the roles of internal and external habit formation in a simple model of endogenous growth with overlapping generations. Unlike the representative agent settings in which the distinction between internal and external habits may not yield significant qualitative differences in working of the model economy, we show that the internal and external habit persistence in overlapping generations economies may have qualitatively different effects on the steady-state characterization as well as on the dynamic behavior of the economy. We also confirm that in an overlapping generations framework, whether the habits in the utility function takes subtractive or multiplicative forms may be critical both for long-run growth and for transitional dynamics.
Keywords: E32; J24; O40; 330; internal habits formation; external habit formation; overlapping generations economy; long-run growth